Efek Kombinasi Pupuk Fosfat dan Bakteri Pelarut Fosfat terhadap Indeks Pertumbuhan Fisiologi Lima Varietas Ubi Jalar [Ipomoea batatas (L.) Lam] - Sukmasari, Miftah Dieni (JURNAL PANGAN, 2016)
Physiological growth index is the representation of plant response to environmental factors. The application of phosphate fertilizers (P2O5) and phosphate solubilizing bacteria (PSB) are environmental factors that can be controlled to optimize plant growth. The effect P2O5 and PSB to sweet potato physiological growth indices has been investigated in the experimental field of the Faculty of Agriculture, Padjadjaran University in June 2014 to October 2014.The trial was designed as 5 x 4 factorial experiments in the randomized complete block and laid out in split-plots arrangements with two replications. The main plots were five sweetpotato varieties (Awachy 1, Awachy 2, Awachy 4, Awachy 5, and Kuningan Putih), while four combination P2O5 + PSB fertilizer levels (36 kg/ha P2O5 without PSB (BP0), 36 kg/ha P2O5 + PSB (BP1), 27 kg/ha P2O5 + PSB (BP2) dan 18 kg/ha P2O5 + PSB (BP3) constituted the sub-plots. The experimental results showed there were variation in crop dry weight (CDW), leaf area index (LAI), net assimilation rate (NAR) and crop growth rate (CGR) caused by a varieties factors. Variety Awachy 5 have the largest physiological growth indices. The application of 18 kg/ha P 2O5 + BPF (BP3) combination increase CDW, LAI, NAR and CGR on sweet potato varieties.